2019
DOI: 10.1016/j.biocel.2018.10.013
|View full text |Cite
|
Sign up to set email alerts
|

CD133 as a regulator of cancer metastasis through the cancer stem cells

Abstract: Cancer stem cells are the cancer cells that have abilities to self-renew, differentiate into defined progenies, and initiate and maintain tumor growth. They also contribute to cancer metastasis and therapeutic resistance, both of which are the major causes of cancer mortality. Among the reported makers of the cancer stem cells, CD133 is the most well-known marker for isolating and studying cancer stem cells in different types of cancer. The CD133high population of cancer cells are not only capable of self-rene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 89 publications
3
75
0
Order By: Relevance
“…Note that KMT2A here could represent expression from normal KMT2A, but in the case of MLLr leukemias will also include MLL-AF4 expression. Interestingly, the PROM1 gene (coding for CD133) is in cluster 2, which matches previous work identifying PROM1 as an overexpressed target of MLL-AF4 that is also more generally expressed in cancer stem cells (84)(85)(86).…”
Section: All and Aml Patient Sub-network Highlight Core Central Trasupporting
confidence: 87%
“…Note that KMT2A here could represent expression from normal KMT2A, but in the case of MLLr leukemias will also include MLL-AF4 expression. Interestingly, the PROM1 gene (coding for CD133) is in cluster 2, which matches previous work identifying PROM1 as an overexpressed target of MLL-AF4 that is also more generally expressed in cancer stem cells (84)(85)(86).…”
Section: All and Aml Patient Sub-network Highlight Core Central Trasupporting
confidence: 87%
“…CD133, encoded by the PROM1 gene, is a pentaspan transmembrane glycoprotein of great potential value as a pancancer target as it is commonly associated with cancer stem cells in multiple different tumor types, including leukemia These authors contributed equally: Laura Godfrey, Nicholas T. Crump [1,2]. Proof-of-principle studies have shown that targeting CD133 can be used to deliver nanoparticles to gastric stem cells [3], or for chimeric antigen receptor T cell therapy in acute lymphoblastic leukemias (ALL) caused by rearrangements of the Mixed Lineage Leukemia (MLL) gene [4].…”
Section: Introductionmentioning
confidence: 99%
“…It may be caused by the regulation of cell growth and proliferation, which causes serious disorder. At the same time, the abnormal expression of tumor related genes, abnormal activation of cell signal transduction, cell proliferation cycle, and cell proliferation cycle were also involved in many aspects [15][16][17]. Cell growth and proliferation in human body are affected and controlled by many factors [18,19].…”
Section: Discussionmentioning
confidence: 99%